Mothers' and fathers' worry and over-control: one step closer to understanding early adolescent social anxiety - Van,Zalk N; Tillfors,M; Trost,K (Child Psychiatry and Human Development, 2018)
This study investigated the links between parental worry, parental over-control and adolescent social anxiety in parent-adolescent dyads. Using a longitudinal sample of adolescents (Mage = 14.28) and their parents (224 mother–daughter, 234 mother–son, 51 father–daughter, and 47 father–son dyads), comparisons were conducted using cross-lagged path models across two time points. We used adolescent reports of social anxiety and feelings of being overly controlled by parents, and mother and father self-reports of worries. Our results show that boys’ social anxiety predicted higher perceived parental overcontrol, whereas girls’ social anxiety predicted higher paternal worry over time. In addition, girls’ reports of feeling overly controlled by parents predicted higher maternal worry but lower paternal worry over time. For boys, feeling overly controlled predicted less social anxiety instead. The study illustrates how mothers and fathers might differ in their behaviors and concerns regarding their children’s social anxiety and feelings of overcontrol.